Antagonistic potential of Trichoderma as a biocontrol agent against Sclerotinia asari - Wang, Zhiqing; Wang, Ziqing; Lu, Baohui; Quan, Xingzhou; Zhao, Guangyuan; Zhang, Ze; Liu, Wanliang; Tian, Yixin (Frontiers in Microbiology, 2022)
In the present study, the inhibitory potential of 14 Trichoderma strains (isolated from Asarum rhizosphere) was investigated against Sclerotinia asari using the plate dilution method. The activ-ity of antioxidant enzymes viz; catalase (CAT), peroxidase (POD), superoxide dismutase (SOD), and malondialdehyde (MDA) in S. asari treated with the two Trichoderma strains was also inves-tigated. Untargeted metabolomic analysis by using LC/MS analysis was carried out to determine differential metabolites in T. hamatum (A26) and T. koningiopsis (B30) groups. Moreover, tran-scriptome analysis of S. asari during the inhibition of S. asari by B30, and A26 compared with the control (CK) was performed. Results indicated that inhibition rates of T. koningiopsis B30, and T. hamatum A26 were highest compared to other strains. Similarly, non-volatile metabolites ex-tracted from the B30 strain showed a 100% inhibition of S. asari. The activity of CAT, SOD, and POD decreased after treatment with A26 and B30 strains while increasing MDA content of S. asari were observed. Antifungal activity of differential metabolites like abamectin, eplerenone, be-henic acid, lauric acid, josamycin, erythromycin, and minocycline exhibited the highest inhibi-tion of S. asari. Transcriptome analysis showed that differentially expressed genes were involved in many metabolic pathways which subsequently contributed towards antifungal activity of Trichoderma. These findings suggested that both Trichoderma strains (B30 and A26) could be ef-fectively used as biocontrol agents against Sclerotinia disease of Asarum.